The effect of “Fishery-PV Integration” on Penaeus monodon culture and research on the micro-ecological environment - Liao, Minze; Long, Xinxin; He, Zihao; Zhao, Jichen; Chen, Xieyan; Zhu, Dongwenjun; Sun, Chengbo (Frontiers in Marine Science, 2022)
“Fishery-photovoltaic (PV) Integration” is a novel aquaculture model that provides enormous potential for aquaculture development. However, research on the aquaculture environment and organisms under the “Fishery-PV Integration” mode is presently sparse. This study investigated Penaeus monodon as a model, studying the growth rates of shrimp, water quality conditions, and the micro-ecological environment. After 105 days of rearing, P. monodon (initial weight of 0.006 ± 0.001 g) reached an average body weight of 11.69 ± 0.92 g. The water quality was stable (C(NH4+) ≤ 1.57 mg/L) during the experimental period. The 16S rRNA gene sequencing results showed that bacterial community structures were significantly distinct among water, effluent and intestinal environments, with a closer relationship between the microbiotas in effluent and water. The dominant phyla present in shrimp intestines, water, and effluent were Proteobacteria, Actinobacteriota, and Bacteroidota. Likewise, Ralstonia, Candidatus Aquiluna, and Vibrio were the dominant genus in the three groups. The relative abundance of Vibrio as a common opportunistic pathogen for shrimp was relatively low, which is beneficial to promote the healthy growth of shrimp. The function of the “Fishery-PV Integration” microbiota was investigated using metagenomic technology. Results showed that microorganisms played an essential role in regulating intestinal amino acids, carbohydrate, and energy metabolisms. Antibiotic resistance genes (ARGs) data indicate that tetH, QnrVC6 and tetX were dominated ARGs in the intestine. At the same time, the ARGs with the highest relative abundance in the water and effluent groups were MexL and adeF. Notably, only 123 ARGs were identified within the “Fishery-PV Integration” pond. This outcome is significantly lower than other studies, indicating that shrimp cultured in the “Fishery-PV Integration” pond had a higher level of food safety. The current study describes the characteristics of the microflora and ARGs distribution in the “Fishery-PV Integration” pond for the first time, providing fundamental information for formulating management strategies for the whole microflora to maintain the health of shrimp.